Bonds of Union : Religion, Race, and Politics in a Civil War Borderland - Ford, Bridget (Book collections on Project MUSE., 2016)
This vivid history of the Civil War era reveals how unexpected bonds of union forged among diverse peoples in the Ohio-Kentucky borderlands furthered emancipation through a period of spiraling chaos between 1830 and 1865. Moving beyond familiar arguments about Lincoln's deft politics or regional commercial ties, Bridget Ford recovers the potent religious, racial, and political attachments holding the country together at one of its most likely breaking points, the Ohio River.